Agricultural mechanization in Ghana: Is specialization in agricultural mechanization a viable business model? - Houssou, Nazaire; Diao, Xinshen; Cossar, Frances; Kolavalli, Shashidhara; Jimah, Kipo; Aboagye, Patrick Ohene (International Food Policy Research Institute, 2013)
Even though the intention of the government is to promote private sector-led mechanization, findings suggest that the AMSEC model is unlikely to be a profitable business model attractive to private investors even with the current level of subsidy. The low tractor utilization rate as a result of low operational scale is the most important constraint to the intertemporal profitability of tractor-hire services. The government can play an important role in facilitating the development of a tractor service market; however, the successful development of such a market depends on the incentive and innovation of the private sector, including farmers who want to own tractors as part of their business portfolio, traders who know how to bring in affordable tractors and expand the market, and manufacturers in exporting countries who want to seek a long-term potential market opportunity in Ghana and in other west African countries.